Testing the volume of HF, HCl, CH4 gaseous air pollutants’ emission for WR water grate boilers type – state of the polish heating industry - Różycka-Wrońska, Ewelina; Wojdyga, Krzysztof (Instal, 2020)
Poland is one of the heaviest users of district heating systems in Europe, and those district heating systems are mainly coal-fired. This study describes the correlation between emission of gaseous air pollutants and the combustion parameters of WR coal-fired water grate boilers (WR-25, WR-10, WR-8M). Air pollution emissions loads were measured during boiler work in conditions other than standard (start-up, extinction, load fluctuations). A negative impact of compounds such as HCl, HF, CO and NH3 in emission standards for various heat sources has been noted.
Keywords: emission; boiler; heating plant; air pollution; combustion; coal; heating